2021
DOI: 10.1111/ger.12585
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Australian dental practices in relation to the ageing population

Abstract: In 2017, 13% of the world population were aged 60 years and older, and this is estimated to increase to 21% by 2050. 1 The Australian population is also rapidly ageing, 2 with almost 17% of Australians aged 65 years or older, 3 and this is projected to reach 25% by the end of 2060. Older individuals may face an increase in life challenges as, with increasing age, structural environment and social isolation often

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Our result indicated Tas with the lowest number of dental visits compared to other states. However, it has the highest percentage of elderly people who live more than 5 km from private and public dental practices and a higher aging population that resides outside of the Greater Capital City areas [ 29 ]. The cost of dental treatment is another factor that may impose a barrier against the utilisation of dental services [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our result indicated Tas with the lowest number of dental visits compared to other states. However, it has the highest percentage of elderly people who live more than 5 km from private and public dental practices and a higher aging population that resides outside of the Greater Capital City areas [ 29 ]. The cost of dental treatment is another factor that may impose a barrier against the utilisation of dental services [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Geographic information systems have been demonstrated as useful tools to assess healthcare accessibility. The literature demonstrates how these techniques can assess gaps in healthcare accessibility in both static analyses [ 7 10 ] and interactive interfaces [ 11 14 ]. The Clinic Planning tool described here builds on this body of work to provide an interactive interface to compare a current state of healthcare locations with a potential future state, providing evidence for the inclusion of healthcare services at new locations.…”
Section: Discussionmentioning
confidence: 99%
“…Kamil, W et al . [ 10 ] use a similar model of accessibility in the Australian context, by making use of the SEIFA measures provided by the ABS to combine both spatial and socio-demographic data. Further research has highlighted the utility of interactive platforms for this field.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recorded hospitalisation growth in our study could be an indicator of a lack of timely and appropriate intervention in the primary care sector. A recent study by Kamil et al also reported an uneven spatial distribution of dental practices in relation to the ageing population, resulting in access issues for some [ 44 ]. Increasing rates of dental hospitalisations among older people could also be an indicator of lack of skills and knowledge in geriatric dentistry among the dental workforces.…”
Section: Discussionmentioning
confidence: 99%